Did anyone notice the transformation of adult social care? An analysis of Safeguarding Adult Board Annual Reports. Issue 1 (9th February 2015) - Manthorpe, Jill; Stevens, Martin; Samsi, Kritika; Aspinal, Fiona; Woolham, John; Hussein, Shereen; Ismail, Mohamed; Baxter, Kate
Abstract : Purpose: – The purpose of this paper is to report on a part of a study examining the interrelationships between personalisation and safeguarding practice. Specifically the authors aimed to examine how safeguarding practice is affected by the roll out of personalisation in adult social care, particularly when the adult at risk has a personal budget or is considering this. Design/methodology/approach: – A sample of annual reports from Adult Safeguarding Boards in England was accessed for content analysis covering the period 2009-2011. One part of this sample of local authorities was selected at random; the other authorities selected had been early adopters of personalisation. The reports were analysed using a pro forma to collect salient information on personalisation that was cross-referenced to identify common themes and differences. Findings: – The authors found variable mentions of personalisation as part of the macro policy context reported in the annual reviews, some examples of system or process changes at mezzo level where opportunities to discuss the interface were emerging, and some small reports of training and case accounts relevant to personalisation. Overall these two policy priorities seemed to be more closely related than had been found in earlier research on the interface between adult safeguarding and personalisation. Research limitations/implications: – There was wide variation in the annual reports in terms of detail, size and content, and reports for only one year were collected. Developments may have taken place but might not have been recorded in the annual reports so these should not be relied upon as complete accounts of organisational or practice developments. Practical implications: – Authors of Safeguarding Adults Board reports may benefit from learning that their reports may be read both immediately and potentially in the future. They may wish to ensure their comments on current matters will be intelligible to possible future readers and researchers. Originality/value: – There does not appear to have been any other previous study of Safeguarding Adult Boards' annual reports. Documentary analysis at local level is under-developed in safeguarding studies.